The new approach of a geolocation information system for offenders in the town of Kananga (British Journal of Multidisciplinary and Advanced Studies, 2023)
This scientific theme addresses the establishment of a geolocation information system for perpetrators of offenses in the town of Kananga. This approach aims to use geolocation technologies to identify and locate people responsible for wrongdoing such as violations of the law in force in the town of Kananga. This system will therefore make it possible to collect precise data on offenders, which will facilitate their identification, prosecution and punishment. The objective is to improve the security and effectiveness of the measures taken to combat crime in the town of Kananga. This system could also help deter criminal acts by providing increased traceability of criminal activity. In this study, we organize our reflection around a few anchor points that we consider with regard to the general argument of this research. Apart from the introduction and the general conclusion, our subject includes four parts, in which we will specifically treat the analysis of the offense in Congolese law and its legal regime, an overview of geolocation (the geographic information system), the deployment of a surveillance camera system in the town of Kananga, as well as the modeling and implementation of a new geolocation system with a view to improving the pursuit of the offender.